Незламність українського народу під час оборони аджимушкайських каменярень - Акіменко, Б. В. (ХНУРЕ, 2019)
In many events of the Second World War Ukrainians showed the features of heroism, self-sacrifice, invulnerability. The mass heroism of the Ukrainian people in the Second World War consists of many examples of heroism of the representatives of the Ukrainian people in battles on earth and in the air, on water and under water, on the fronts and in partisan detachments, underground hostile territories, in the rear at the factories and collective farms fields. Defense of the Adzhimushkay quarry as an example of invincibility of Ukrainians is considered in this work.